2020
DOI: 10.3389/fmicb.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Plant-Microbe System: Pisum sativum (L.) Cadmium-Tolerant Mutant and Rhizobium leguminosarum Strains, Expressing Pea Metallothionein Genes PsMT1 and PsMT2, for Cadmium Phytoremediation

Abstract: Two transgenic strains of Rhizobium leguminosarum bv. viciae, 3841-PsMT1 and 3841-PsMT2, were obtained. These strains contain the genetic constructions nifH-PsMT1 and nifH-PsMT2 coding for two pea (Pisum sativum L.) metallothionein genes, PsMT1 and PsMT2, fused with the promoter region of the nifH gene. The ability of both transgenic strains to form nodules on roots of the pea wild-type SGE and the mutant SGECd t , which is characterized by increased tolerance to and accumulation of cadmium (Cd) in plants, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…In the present study, the fusion of symbiosomes and degeneration of bacteroids within them led to the formation of "ghost" bacteroids in the TMTD-sensitive cultivar 'Finale' (Figure 12A,B). Similarly, symbiosome fusion and the formation of multiple symbiosomes were found to occur in response to copper exposure in M. lupulina nodules [70,90] and cadmium exposure in pea nodules [49,50]. In the present study, we observed the accumulation of PHB in the symbiosomes in bacteroids, bacteroid contraction, an increase in the peribacteroid space, and destruction of symbiosome membranes as a result of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the present study, the fusion of symbiosomes and degeneration of bacteroids within them led to the formation of "ghost" bacteroids in the TMTD-sensitive cultivar 'Finale' (Figure 12A,B). Similarly, symbiosome fusion and the formation of multiple symbiosomes were found to occur in response to copper exposure in M. lupulina nodules [70,90] and cadmium exposure in pea nodules [49,50]. In the present study, we observed the accumulation of PHB in the symbiosomes in bacteroids, bacteroid contraction, an increase in the peribacteroid space, and destruction of symbiosome membranes as a result of lipid peroxidation.…”
Section: Discussionsupporting
confidence: 71%
“…Polyhydroxybutyrate protects cells from diverse stresses, including heat shock, ultraviolet radiation, oxidizing agents, and osmotic shock [84]. Previously, we observed accumulation of PHB in bacteroids in response to cadmium exposure [49,50].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two recombinant strains of R. leguminosarum bv. Viciae , each expressing a pea metallothionein gene, PsMT1 or PsMT2 , led to normal development of nodules in pea under Cd stress [ 35 ]. Because the heavy metals cause oxidative stress [ 136 ], the other strategies could be based on maintaining the homeostasis of metals through different mechanisms [ 133 ].…”
Section: Improvement Of Rhizobial Strainsmentioning
confidence: 99%
“…The mutant SGECd t is characterized by an increased tolerance to cadmium and elevated cadmium accumulation [ 184 ]. The mutant demonstrates a higher tolerance to cadmium, both in terms of nodulation [ 185 , 186 ] and the functioning of established nodules [ 187 ].…”
Section: Use Of Non-symbiotic Mutants To Study Nodulationmentioning
confidence: 99%